Is multidisciplinary management possible in the treatment of lung cancer? A report from three Italian meetings - Franceschini, Davide; Bruni, Alessio; Borghetti, Paolo; Giaj-Levra, Niccolò; Ramella, Sara; Buffoni, Lucio; Badellino, Serena; Andolina, Maria; Comin, Camilla; Vattemi, Emanuela; Bezzi, Michela; Trovò, Marco; et al. (Radiologia medica, 2020)
Purpose To report criticisms and barriers to the “real-life” application of international guidelines and recent developments in the management of locally advanced non-small cell lung cancer (NSCLC) in Italy. Methods Three 2-day courses were organized. During the first day, experts in different fields of thoracic oncology gave their lecture on diagnosis and therapy for locally advanced NSCLC. During the second day, all participants were divided into four groups to discuss on a clinical case as a multidisciplinary team (MDT). The aim was to stimulate the discussion on practical issues in the management of NSCLC patients in the real-life practice. Results A total of 196 physicians were involved in the courses as learners. Invasive diagnosis of nodal disease for staging purposes, a priori definition of “surgical resectability” and a regular MDT with all crucial participants available were the three main key points identified for a good management of these patients. The main barriers to the clinical application of a good diagnostic and therapeutic approach to the patient were the absence of a regular and complete MDT in the South and Centre of Italy, while in the North of Italy, time for discussion of clinical cases in the MDT and waiting lists for staging and therapeutic interventions were deemed as the major concerns. Conclusion The meetings showed that diagnosis and treatment of locally advanced NSCLC are still extremely variable between different Italian regions. Logistic issues, waiting lists, paucity of well-trained staff and expertise seem to be the main barriers to international guidelines application.